Efforts To Improve Reading Skills Using The Picture And Picture Method By Utilizing Word Card Media In Indonesian Language Learning - Agustina, Agustina; Herman, Herman; Riadin, Agung (International Journal of Universal Education, 2023)
Reading is a means for students to learn something that is not yet known and can expand knowledge, and students can recognize written messages contained in reading. Beginning reading is done in early grade so students can read simple words and sentences fluently and precisely. Picture and Picture learning method is a form of learning method that uses picture cards paired/sorted into a logical sequence is one of the media that can help students to improve reading skills. This research was conducted to improve reading skills through the picture and picture method by utilizing word card media in Indonesian class I subjects at Elementary School 2 Kapuas Tengah in the 2021/2022 academic year. This research is classroom action research. The subjects of this study were first-grade students at Elementary School 2 Kapuas Tengah. Data collection techniques using tests. The data analysis technique used was descriptive quantitative. The results showed that the test results in the first cycle were only 20 (50%) students who achieved individual mastery. If you look at the classical completeness in this cycle, it is also incomplete because 20 students (50%) have not finished. In the second cycle, 35 students (87.5%) have completed while five (12.5%) have not completed their studies